Utilizing Islamic Historical Perspectives in Managing Global Uncertainty to Win The Future - A’la, Abd (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The contemporary world faces unprecedented global uncertainty manifested in economic instability, environmental degradation, technological disruption, and ideological conflict. This paper explores how Islamic historical experiences—particularly during the life of the Prophet Muhammad (PBUH)—can offer valuable insights for addressing these uncertainties. Drawing parallels between early Islamic crises and current global challenges, the article demonstrates how strategic decisions rooted in faith, collaboration, trust, and resilience enabled the Muslim community to thrive amidst adversity. Events such as the Prophet’s migration (Hijrah), the Battle of Uhud, and the Treaty of Hudaybiyyah exemplify the use of contextual, emotional, inspirational, and physical intelligence in navigating uncertainty. The paper argues that embracing uncertainty is essential, not as a passive condition, but as a call for ethical action, trust-based cooperation, and moral leadership. Moreover, Islam offers not only spiritual guidance but also a framework for environmental stewardship and social justice. By revisiting these foundational Islamic values, contemporary societies—especially Muslim communities—can build inclusive, peaceful, and sustainable futures. The paper concludes by asserting that Muslims, particularly in Indonesia, are well-positioned to lead global efforts in embracing uncertainty, cultivating resilience, and advancing universal well-being grounded in ethical and historical wisdom.